The banking system of Kazakhstan in the framework of regional integration - Мырзахметова, А. М. (Journal of Economic Research & Business Administration, 2016)
This article is devoted to actual issues - the study of the development of the banking system of Kazakhstan in the conditions of deepening of integration processes. In work the analysis of the formation and further development of the domestic banking system. As a research task, the au-thor has identified a number of key aspects of successful functioning in integrative associations, such as the vehicle CU and, based on it, the EEU. The focus in the article the author focuses on the role of the state reform of the financial system, in order to overcome the negative consequences of the global economic crisis and building a sustainable banking system of Kazakhstan. The study gives a generalized description of the advantages, disadvantages and current trends of activity of Kazakhstan banks. The ar-ticle summarizes some of the results of assessment of competitiveness and the specificity of banks in the scale of regional integration.